Ammonia-removal efficiency of a novel Acinetobacter calcoaceticus strain isolated from industrial wastewater of Ninh Binh coal nitrogenous fertilizer plant - Cuong, Do Bien; Han, Hoang Ngoc; Thiem, Pham Van (Vietnam Journal of Science and Technology, 2018)
Ammonium removal from wastewaters has recently became a major concern of fertilizer manufacturers and industrial zones in Vietnam. Using aerobic ammonium remover may be a appreciate solution for reduction of treatment cost. This study describes the isolation and characterization of a novel bacterium for ammonium removal under aerobic conditions. Twelve ammonium remover strains were isolated from wastewater of a local fertilizer industry. The isolated strains were initially screened using solid media for their nitrifying activities. Among them two of the bacteria displayed the highest removal of ammonium without much accumulation of nitrite and nitrate. The isolates were identified as Acinetobacter based on biochemical characteristis and 16S rRNA sequence. One of these two isolates, Acinetobacter calcoaceticus A8 strain, showed 88% ammonium removal from industrial fertilizer wastewater.